2019
DOI: 10.1016/j.micpath.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

cGAS-STING responses are dampened in high-risk HPV type 16 positive head and neck squamous cell carcinoma cells

Abstract: Head and neck cancers (HNCs) are a major health problem and a leading cause of morbidity and mortality worldwide. More than 90% of these tumours are head and neck squamous cell carcinomas (HNSCCs). Amongst the common risk factors for HNCs (tobacco and alcohol use), there is a strong association of human papillomavirus (HPV) with HNSCCs. HPV type 16 (HPV 16), the major high-risk HPV type, is most commonly associated with HPV-driven HNSCCs. The promiscuous nature of the major HPV oncogene, E7, allows its interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 26 publications
1
34
0
5
Order By: Relevance
“…No estudo epidemiológico-clínico de Mushfiq et al 32 foi enfatizado que os tumores associados ao HPV-16 e HPV-18 localizados na língua e na área gengival podem ocasionar consequências mais graves para os pacientes, como, por exemplo, incapacidade de deglutir, mastigar e dificuldades durante a emissão da fala, sendo que elevados índices de mortalidade são associados aos cânceres epidermoides bucais que se desenvolvem na região lingual 28 .…”
Section: Sítios Bucais Mais Afetados Pelo Cebunclassified
See 2 more Smart Citations
“…No estudo epidemiológico-clínico de Mushfiq et al 32 foi enfatizado que os tumores associados ao HPV-16 e HPV-18 localizados na língua e na área gengival podem ocasionar consequências mais graves para os pacientes, como, por exemplo, incapacidade de deglutir, mastigar e dificuldades durante a emissão da fala, sendo que elevados índices de mortalidade são associados aos cânceres epidermoides bucais que se desenvolvem na região lingual 28 .…”
Section: Sítios Bucais Mais Afetados Pelo Cebunclassified
“…Entretanto, barreiras sociais ainda precisam ser ultrapassadas para que esses profissionais consigam intervir de maneira eficaz em fatores determinantes para o processo de saúde-doença de seus pacientes [33][34][35] . Tais barreiras incluem, principalmente, a dificuldade da abordagem de assuntos relacionados a doenças sexualmente transmissíveis, como o HPV [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: A Importância Da Atuação Do Cirurgião-dentistaunclassified
See 1 more Smart Citation
“…2 90% of HPV-positive OP cancers are infected with high-risk HPV16 (the dominant subtype). 6 In cancers associated with HPV infection, the viral oncoproteins E6 and E7 are always overexpressed. E7 can bind to the retinoblastoma (Rb) protein and destroy the E2F/Rb complex.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that regardless of the HPV infection status in the oropharynx, p16 protein can independently serve as a predictor of radiotherapy response. 6,7 Among patients undergoing surgery and postoperative adjuvant radiotherapy, the overall survival and disease-specific survival of patients with positive p16 protein were significantly longer than those with negative p16. 8 The results shown in our univariate analysis are consistent with it.…”
mentioning
confidence: 99%